Strengthening of slab with openings located in the shear zone with CFRP sheets and anchors - Cheang, Yee (2016)
This thesis deals with strengthening of slab with openings located in the shear zone with CFRP sheets and anchors. The objective of this thesis is to determine the behavior of reinforced concrete slab with opening located in the shear zone in terms of load deflection behavior and crack pattern, to evaluate the performances of CFRP sheets and anchors in strengthening of reinforced concrete slabs with openings, and to validate finite element results with experimental results. The thesis uses finite element software, Abaqus version 6.14 from Dassault Systèmes to simulate various configuration of CFRP anchors. The best configuration of CFRP anchors that resulted in highest ultimate load was identified and validation of results was conducted. The material model employed during the finite element analysis was Brittle Cracking model. From the finite element analysis, the highest ultimate load was achieved on slab with opening strengthened with CFRP sheets and anchors. The ultimate load was 58.39 kN, about 202.07 % higher than unstrengthen slab with opening. In experiment, slab with opening strengthened with CFRP sheets had the highest ultimate load among all laboratory specimens. The ultimate load was 15.74 kN, about 10.79 % greater than unstrengthen slab with opening. In terms of crack patterns, for slab without opening, slab with opening and slab with opening strengthened with CFRP had exhibited similar crack pattern, with only a visible vertical crack at the mid-span. Meanwhile, for slab with opening strengthened with CFRP and anchors, two visible cracks were detected at the middle region of the slab. The locations of crack were as predicted in Abaqus, since the stress around these regions was the highest. Finite element and laboratory test results show that both CFRP sheets and CFRP anchors were able to increase the ultimate load of slab with opening. However, in finite element analysis, a combination of CFRP sheets and anchors were found more effective in strengthening than by only using CFRP sheets, however the laboratory test results showed otherwise. This is due to the assumptions of perfect bond between CFRP sheets and concrete surface in Abaqus, and excessive stress inducted to the sample during drilling works.